Clinical high risk and first episode schizophrenia: Auditory event-related potentials. Issue 2 (28th February 2015) - del Re, Elisabetta C.; Spencer, Kevin M.; Oribe, Naoya; Mesholam-Gately, Raquelle I.; Goldstein, Jill; Shenton, Martha E.; Petryshen, Tracey; Seidman, Larry J.; McCarley, Robert W.; Niznikiewicz, Margaret A.
Abstract: The clinical high risk (CHR) period is a phase denoting a risk for overt psychosis during which subacute symptoms often appear, and cognitive functions may deteriorate. To compare biological indices during this phase with those during first episode schizophrenia, we cross-sectionally examined sex- and age-matched clinical high risk (CHR, n =21), first episode schizophrenia patients (FESZ, n =20) and matched healthy controls (HC, n =25) on oddball and novelty paradigms and assessed the N100, P200, P3a and P3b as indices of perceptual, attentional and working memory processes. To our knowledge, this is the only such comparison using all of these event-related potentials (ERPs) in two paradigms. We hypothesized that the ERPs would differentiate between the three groups and allow prediction of a diagnostic group. The majority of ERPs were significantly affected in CHR and FESZ compared with controls, with similar effect sizes. Nonetheless, in logistic regression, only the P3a and N100 distinguished CHR and FESZ from healthy controls, suggesting that ERPs not associated with an overt task might be more sensitive to prediction of group membership. Highlights: ERPs in clinical high risk (CHR) and first episode schizophrenia (FESZ) N100, P3a, P3b ERPs similarly decreased in both CHR and FESZ (77 characters with spaces) Only N100 and P3a distinguish CHR and FESZ from HC in regression modeling (75 characters with spaces)